Kajian q.s ali imran (3): 64 dan al baqarah (2): 286 - putri, eka julia (Maliki Interdisciplinary Journal, 2026)
This study analyzes the messages of preaching and spiritual resilience contained in Q.S Ali Imran (3): 64 and Q.S Al Baqarah (2): 286. This study uses a qualitative approach and thematic interpretation, where Q.S Ali Imran:64 presents a dialogue-based da'wah approach and the meeting point of tawhid, as well as observing and emulating the da'wah of the Prophet Muhammad, peace be upon him, as described in the surah. Meanwhile, Surah Al-Baqarah: 286 provides psychological reinforcement to humans through the principle that every test that comes in their lives is in accordance with the capabilities and abilities of the servant. This principle will have a positive impact on the psychology of a servant, because Allah has assured them through this verse not to give up easily and feel that the trials they face cannot be overcome. The results of this study show that these two verses have a normative connection in building harmonious and humanistic da'wah while increasing the mental resilience of each individual. The values contained in these two verses are relevant to addressing the various challenges, diversity, and social pressures experienced by modern society. This study also emphasizes and affirms the relevance of the teachings of the Qur'an in building a tolerant society and individuals who have empathy, as well as building mental resilience in facing various challenges in life